HUBUNGAN STATUS GIZI DENGAN KEJADIAN HIPERTENSI PADA USIA 26 – 59 TAHUN DI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Humairah, Anugerah; Puspa Anggraini, Shelly; Iqra Fikha, Idri; Jelsa Nabilah, Okta (Ensiklopedia of Journal, 2025)
Non-communicable diseases (NCDs) that are the leading cause of death globally include cardiovascular diseases. The majority of cardiovascular diseases are caused by controllable risk factors, among which is hypertension. Hypertension is an increase in arterial blood pressure where systolic blood pressure is equal to or greater than 140 mmHg and/or diastolic blood pressure is equal to or greater than 90 mmHg. Hypertension is known as the "silent killer" because it often presents without symptoms. WHO has recorded that at least 1.28 billion adults aged ≥18 years worldwide suffer from hypertension, with the majority (two-thirds) living in low- and middle-income countries. It is estimated that 46% of adults with hypertension are unaware of their condition. Less than half (42%) of adults with hypertension are diagnosed and treated, and only about 1 in 5 adults (21%) with hypertension are able to control it. Hypertension is a leading cause of premature death globally. One of the global NCD targets is to reduce the prevalence of hypertension by 33% between 2010 and 2030. One of the suspected risk factors influencing the incidence of hypertension is nutritional status. Research shows that individuals who are overweight are at greater risk of developing hypertension compared to those with a lower body weight. Overnutrition increases the risk of hypertension for several reasons. The larger the body mass, the more blood is needed to supply oxygen and nutrients to body tissues. This leads to an increase in blood volume circulating through blood vessels, which in turn exerts greater pressure on artery walls, potentially causing an increase in blood pressure. In addition, excess body weight also raises heart rate frequency. This study aims to determine the relationship between nutritional status and the incidence of hypertension in individuals aged 26–59 years at Pekanbaru Medical Center Hospital. This research uses a quantitative approach with a cross-sectional design. The sample consisted of 102 respondents selected using quota sampling. Data were analyzed using the Chi-Square test. The results showed no significant relationship between nutritional status and the incidence of hypertension (p = 0.579).Keywords: Hypertension, Nutritional Status, Age 26–59 Years